Optimizing Employee Experience and Coaching to Reduce Turnover Intention: A Growth Mindset Moderation Study in Leasing Companies - Omega, Agata Mia Wira; Putranta, Martinus Parnawa; Pramudianto, Pramudianto (KINERJA, 2024)
Generation Y and Generation Z have been entering workplace and dominating various jobs in organizations. These two cohorts share similar characteristics including, among other things, the need of self-development and the need of challenging jobs that enable them to avoid boredom. When these needs are not met their desires to leave the organization is likely to occur. Providing positive personal experience and proper coaching at work may help resolve the aforementioned negative consequence. This research aimed to address this issues. A sample of 182 of employees from the two cohorts who worked for leasing companies in Yogyakarta participated in the research. Purposive sampling was adopted to invite respondent participation. An online survey was employed to gather the data. The PLS-SEM method was used to analyze the data . Findings of the research show that employee experience and leadership coaching skills have a negative influence on turnover intention. A growth mindset strengthens the negative impact of employee experience on turnover intention. However, a growth mindset was found not to have any moderating influence on the effect of leadership coaching skills on turnover intention. Managerial and scholarly implication are then outlined.